Frontiers and future of immunotherapy for pancreatic cancer: from molecular mechanisms to clinical application - Zheng, Rui; Liu, Xiaobin; Zhang, Yufu; Liu, Yongxian; Wang, Yaping; Guo, Shutong; Jin, Xiaoyan; Zhang, Jing; Guan, Yuehong; Liu, Yusi (Frontiers in Immunology, 2024)
Pancreatic cancer is a highly aggressive malignant tumor, that is becoming increasingly common in recent years. Despite advances in intensive treatment modalities including surgery, radiotherapy, biological therapy, and targeted therapy, the overall survival rate has not significantly improved in patients with pancreatic cancer. This may be attributed to the insidious onset, unknown pathophysiology, and poor prognosis of the disease. It is therefore essential to identify and develop more effective and safer treatments for pancreatic cancer. Tumor immunotherapy is the new and fourth pillar of anti-tumor therapy after surgery, radiotherapy, and chemotherapy. Significant progress has made in the use of immunotherapy for a wide variety of malignant tumors in recent years; a breakthrough has also been made in the treatment of pancreatic cancer. This review describes the advances in immune checkpoint inhibitors, cancer vaccines, adoptive cell therapy, oncolytic virus, and matrix-depletion therapies for the treatment of pancreatic cancer. At the same time, some new potential biomarkers and potential immunotherapy combinations for pancreatic cancer are discussed. The molecular mechanisms of various immunotherapies have also been elucidated, and their clinical applications have been highlighted. The current challenges associated with immunotherapy and proposed strategies that hold promise in overcoming these limitations have also been discussed, with the aim of offering new insights into immunotherapy for pancreatic cancer.